Analysis of business intelligence systems transmission session - Ahmadzai, Abdul Shabir; Yazdani, Qurban; Abubakar Ibrahim, Adamu (University of Science and Technology, 2022)
Information and Communication Technology (ICT) is the central part of Intelligent systems. Business Intelligence (BI) utilizes ICT resources and capabilities to enhance decision-making from the available information. One of the core components of ICT resources is the network. Hypertext Transfer Protocol (HTTP) is an application layer protocol in a network model responsible for handling "requests" in a transmission session. Transmission Control Protocol (TCP) establishes connections session and keeps track of the state of the communication session. Unfortunately, a request from a critical online transaction over TCP in a BI environment is bound to face some uncertainty. There is a lack of studies on the impact of communication over transmission sessions on BI operations. This paper presented an experimental evaluation of the BI transaction transmission session. Various transactions were performed to monitor andanalyze the request made with HTTP over a TCP transmission session. Both the HTTP and TCP features for all transactions were captured. The finding indicates that time is highly associated with less traffic congestion and transaction overhead